2000
DOI: 10.1243/0957650001538146
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies of unsteady flows in a centrifugal compressor stage

Abstract: This paper describes the flow analysis in a centrifugal compressor stage using a threedimensional computational fluid dynamics (CFD) algorithm. The flow unsteadiness arising from the interaction between the impeller and the diffuser has also been analysed using an algorithm suitable for equal or multiple numbers of rotor and diffuser blades. The multi-block, structured grid CFD code TASCflow which provides an approximate solution to the Reynolds-averaged Navier-Stokes equations was used as a basis and algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…With further reduction up case (4) in the cavitation parameter, the tip-vortex cavitation has been more produced; the generated pump head still remains, however, constant without severe performance degradation. When the net positive suction head (NPSH) reaches a sufficiently low value over the 'knee' of nearly constant head coefficient (for cases (5) and (6)), the distortion of the flow pattern, by mixing more tip-vortex cavitation with the main flow between the impeller blades, extends across the flow channel and consequently leads to a sudden decrease in the total pressure rise. Comparing with the computational results, it is observed that the cavitating region is spread out over the suction surface as well as the leading edge of the impeller blade.…”
Section: Cavitation Performance Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…With further reduction up case (4) in the cavitation parameter, the tip-vortex cavitation has been more produced; the generated pump head still remains, however, constant without severe performance degradation. When the net positive suction head (NPSH) reaches a sufficiently low value over the 'knee' of nearly constant head coefficient (for cases (5) and (6)), the distortion of the flow pattern, by mixing more tip-vortex cavitation with the main flow between the impeller blades, extends across the flow channel and consequently leads to a sudden decrease in the total pressure rise. Comparing with the computational results, it is observed that the cavitating region is spread out over the suction surface as well as the leading edge of the impeller blade.…”
Section: Cavitation Performance Characteristicsmentioning
confidence: 99%
“…This article focuses on the hydraulically detailed performance analysis, including the cavitation phenomena, of a mixed-flow pump for marine waterjet propulsion. Thus, the present study has employed the well-established commercial computational fluid dynamics (CFD) codes [3,4], whose predictive capabilities have already been validated in the open literature and a variety of industrial applications: unsteady flow computation in a centrifugal compressor [5], CFD application to internal flow analysis of a waterjet pump [6], design and performance analysis of a centrifugal blood pump [7], and hydraulic performance analysis of axial-flow pump [8] and radial-inflow turbine [9].…”
Section: Introductionmentioning
confidence: 99%
“…Using the 3D CFD viscous code TASCFlow, they were able to simulate the gasdynamic process of the whole centrifugal compressor stage (impeller, diffuser, and volute) and obtain results that accurately matched the experimental ones. The same commercial code was used by Koumoutsos and his team in the study of unsteady flows in centrifugal compressors [3]. Their conclusions suggest that even though the unsteady simulation is much more accurate and captures better the phenomena inside the centrifugal compressor stage, a steady solution will provide results accurate enough to be used as valid predictions in the design process.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows an impeller model with four vanes used in the test pump of the present work for the trial run. Over the recent years, several researchers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] have taken much effort to develop hydroturbomachines for performance enhancement through the study of different configurations of several hypothetical flow analyses. From the literature review and general insights acquired by the in-depth study of pump impeller, the most influencing design variables are impeller width, impeller eye diameter, number of vanes, and vane outlet angle for enhancing pump performance [26].…”
Section: Test Pump With Impellermentioning
confidence: 99%